Comparison of iridial pigmentation between latanoprost and isopropyl unoprostone: a long term prospective comparative study. Issue 8 (24th July 2003) - Chiba, T; Kashiwagi, K; Chiba, N; Ishijima, K; Furuichi, M; Kogure, S; Abe, K; Tsukahara, S
Abstract : Aim: To compare incidence of iridial pigmentation prospectively induced by long term treatment with latanoprost and isopropyl unoprostone (hereafter, unoprostone) in Japanese patients with glaucoma. Methods: Patients with glaucoma treated with prostaglandin (PG) related ophthalmic solutions were sequentially enrolled. Patients treated for more than 30 months with PG related ophthalmic solutions were subjected to analysis. The entry criteria were no history of intraocular surgery, laser iridotomy, and/or laser trabeculoplasty within 12 months before and after the enrolment; and no history of uveitis; no changes in antiglaucoma drugs within 6 months before and after the enrolment. Photographs of the irides were taken under the same conditions and three glaucoma specialists evaluated the iridial pigmentation with masking of patient information. The correlation of iridial pigmentation with the background factors and the reduction of intraocular pressure (IOP) before and after the treatment were investigated. Results: 48 eyes in 48 patients satisfied the enrolment criteria (25 eyes in the latanoprost group, 23 eyes in the unoprostone group). At the end of the follow up period, iridial pigmentation was present in 15 patients (60.0%) in the latanoprost group and seven patients (30.4%) in the unoprostone group. The correlation between development of iridial pigmentation and age, sex, concurrent use of other ophthalmic solutions, and IOP reduction was not significant. Conclusions: The incidence of iridial pigmentation induced by latanoprost or unoprostone is high in the case of long term treatment. Iridial pigmentation did not affect PG related ophthalmic solution induced IOP reduction.